The Effectiveness of Teaching Energy in a Secondary School Using the "Factory of Ideas" Teaching Approach. Issue 1 (2nd January 2021) - Koma, Sechaba; Mokuku, Ts'epo; Makatjane, Tiisetso J.; Balck, Christel; Sermeus, Jan
Abstract : This study investigated the extent to which the proposed Factory of Ideas (FOI) teaching approach impacted on students' understanding of energy based on their prior knowledge. The FOI is a didactic approach that, unlike the classic cognitive conflict approach, employs a variety of activities to offer students a scientific conception for comparison with their own, and to expose students to several contexts in which the concept is applied. A total of 122 Grade 8 students participated in the study. A quasi-experimental research design with both a pre–post-test and a control and experimental group was employed. The control group (an intact class, N  = 58) was taught using traditional teaching methods while the experimental group (an intact class, N  = 64) was taught using the FOI teaching approach, which is underpinned by tenets of argumentation theory. The content-based pre- and post-test produced quantitative data that were analysed using SPSS. Based on the t -test comparing the mean scores of the two groups after the intervention, the experimental group was consistently found to outperform the control group on the correct understanding of energy concepts. Thus the FOI teaching approach impacted significantly on students' understanding of energy concepts. However, for some students, the FOI did not significantly change the students' use of alternative conceptions related to the law of conservation of energy. It is concluded that the FOI strategy is in general an effective teaching strategy, with the potential to facilitate learning of new scientific concepts, particularly if supported by a number of relevant science applications, and by laboratory and visual resources.